Pemberdayaan Kader Dan Keluarga Untuk Mencegah Kejadian Jatuh Pada Lansia Pasca Stroke - Nurhasanah, Aan; Nur, Aan; Hartini, Tien (INSTITUT KESEHATAN DELI HUSADA, 2023)
Stroke is a disease caused by interruption of blood flow to the brain or blood flow to the brain stops. The impact of a stroke can cause disability and will affect daily activities. One of the physical problems caused by elderly stroke patients is falling. There is a risk of falling because sufferers experience disability, loss of sensation, decreased ability to coordinate the body, decreased muscle function which results in a decrease in the ability to support, hold and balance body mass, and difficulty in directing, measuring the speed of the ability of muscles to maintain body balance. Family support is something that needs to be considered in the management of stroke patients because it plays a very important role in patient adherence to undergoing rehabilitation to prevent re-stroke. The purpose of this community service activity is to empower families and cadres in an effort to prevent falls in the elderly after a stroke so as to reduce the number of falls. in the elderly in carrying out their daily activities. Strategy Activities are carried out by means of training using PPT, and videos for 2 days followed by mentoring for 4 weeks involving 6 cadres, 24 families with post-stroke elderly, so a total of 30 people. Results There is an increase in family knowledge and attitudes and skills in preventing post-stroke falls in the elderly